The effect of using an assistive device in learning the forehand and backhand strokes in tennis at various ages. The effect of pendulum training exercises on improving some physical and skill-related attributes of the University of Babylon football team players. - Jawad, Asst.L. Iman Mohammed Hamid; Taher, L. Coach Zeina Alaa; Sabri, L.Coach Zulfiqar Jamal (Sulaimani Journal for Humanities, 2026)
This study aimed to develop standardized pendulum training exercises to improve certain physical and skill-related attributes in young football players. The researchers used an experimental approach with a total sample size of 25 players, from which they intentionally selected 20. The study concluded that standardized pendulum training exercises are highly effective in improving certain physical and skill-related attributes in young football players. Furthermore, a significant relationship exists between the explosive power of the kicking leg and the shooting accuracy of players from Babylon Football Club. Finally, a significant relationship exists between the speed-strength of the kicking leg and the shooting accuracy of players from Babylon Football Club. The study also found a significant relationship between the speed-strength of the kicking leg and the shooting accuracy of players from Babylon Football Club. The researchers recommended emphasizing structured exercises based on pendulum training in developing the physical and technical abilities of football players; emphasizing the importance of explosive power training and its development due to its significance in improving shooting accuracy for football players; and emphasizing the importance of speed-strength training and its development due to its significance in improving shooting accuracy for football players.